Aktivitas Hepatoprotektor Cuka Apel 'A' terhadap Kadar SGOT dan SGPT Serum Tikus Wistar yang Diinduksi Parasetamol Dosis Toksik (Hepatoprotector Activities of 'A' Apple Vinegar to SGOT and SGPT Serum in Wistar Rats Induced by Toxic Dose of Paracetamol) - Fawziyah Putri Maulida; Hairrudin Hairrudin; Elly Nurus Sakinah (Pustaka Kesehatan, 2016)
The use of a toxic dose of paracetamol is able to generate free radicals in the form of N-acetyl-p-benzoquinoneimine (NAPQI) resulting in increased levels of hepatic transaminase enzymes, Serum glutamate oksaloasetat transaminase (SGOT) and serum glutamate pyruvate transaminase (SGPT). 'A' apple vinegar contains antioxidants such as polyphenols, and vitamin C as well as acetic acid that were thought to have hepatoprotector effect which expected to prevent liver damage caused by NAPQI. The purpose of this study was to determine hepatoprotective activity of 'A' apple vinegar to SGOT and SGPT serum levels in wistar that induced by toxic dose of paracetamol. This study used 27 wistars wich were divided into three groups. The results of this study showed that average values of SGOT/SGPT in the normal control group were 79.00/113.89, negative control group were 289.67/296.22, treatment group were 180/194.44. Statistical test performed by using One Way Anova test for SGOT data and Kruskal Wallis test for SGPT. From the results it can be concluded that the administration of 'A' apple vinegar has hepatoprotective activity to SGOT and SGPT serum levels in wistar rats induced by toxic dose of paracetamol. Keywords: Apple vinegar, hepatoprotector, antioxidant, Paracetamol, Transaminase